PENGARUH PENGENDALIAN INTERNAL TERHADAP TINGKAT KREDIT MACET DALAM PROSES PEMBIAYAAN SEPEDA MOTOR PT RADANA FINANCE CABANG TANGERANG KOTA, BANTEN - Kusumawati, Nugrahini; Jimmi, Jimmi (Universitas Serang Raya, 2015)
The purpose of this research is to determine the effect of internal control on the level of bad loans and the influence on the level of bad debts the motorcycle in PT Radana Finance branch Tangerang city, Banten. A method of analysis of data used is a questionnaire survey method with Likert scale. Data taken with taking samples obtained from employees at PT Radan Finance branch tangerang city for seven days using the formula slovin by 44 employees. Furthermore, using SPSS v.19 software and statistical formulas to determine the influence of the two variables, namely internal control (x) and loans (y). Ther result showed that there is a very strong influence of internal control (x) with bad credit (y). With Pearson correlation value of 0.884. Then the contribution of internal control variable (x) against non-performing loans (y) of 0,703, or 70.3%, while the remaining 29.7% influenced by other factors not described. And the linear regression equation obtained was Y =75.268-0,548X. In a hypothesis test based on the t-test is concluded Ho is rejected and Ha accepted. Means of internal control variable (x) has a strong influence on the variable sangta loans (y). It was on the show from the value t is greater than t table (9.980> 2021). This means that